The effectiveness of training programs in improving employee performance at PT. TI Matsuoka winner industry (TIMW) - Gowasa, Verliyani; Aswan, Mukhamad Kholil (ProBisnis : Jurnal Manajemen, 2025)
The research objectives are: find out the implementation, effectiveness and inhibiting factors in training programs at PT. IT Matsuoka Winner Industry. The research method used is descriptive qualitative with in-depth interview techniques Human Resource Development (HRD) and employees. The research results show 1) Implementation of training programs at PT. Matsuoka Winner Industry begins with planning employee training programs which are carried out systematically and based on needs. The process begins with implementation Training Need Analysis (TNA) at the beginning of each year, 2) Implementation of training programs at PT. Matsuoka Winner Industry has been implemented effectively, this can be seen from employees who are able to work faster and better than before, and 3) Factors that hinder the training program at PT. Matsuoka Winner Industry, namely time allocation, training costs, and facilities used during training